REPRESENTASI GAYA LOKAL DALAM PERTUNJUKAN KACAPING SEBAGAI REFLEKSI NILAI PENDIDIKAN BUDAYA MANDAR - Ihsan, Andi; Saputra, Andi Taslim (JURNAL PAKARENA, 2024)
This research aims to understand the representation of local style in Kacaping performances on the festival stage as a critical reflection of the educational values of Mandar Culture. There have been several studies on kacaping, but generally, they only focus on music analysis, development, biography, and do not explain the representation of local style as a critical reflection of the educational values of the Mandar community in festival stage performances. This research aims to determine: a) the representation of local style on the festival stage; b) the relationship between the local style represented in the kacaping performance and the critical reflection of the educational values of the Mandar community. This research uses a qualitative method with an ethnographic study approach on kacaping performances as a research design that combines musical and non-musical elements. The subject of this research is the performance presented by Satuni at various festivals, particularly at the Oni-Oni Kacaping Festival. Data collection techniques were obtained through preliminary studies, audio and video analysis, and interviews. The research results show that: 1) the representation of local style in Kacaping performances interprets the relationship with a critical reflection of educational values, both musically and non-musically, involving speech (comedy) and singing styles that are identical to the Mandar culture, which contains critical reflections; 2) Kacaping not only serves as an entertainment filler but also reflects the uniqueness and beauty of Mandar culture. The conclusion shows that the representation of local style in Kacaping performances at international festivals, both musically and non-musically, not only reflects but also demonstrates the role of the Kacaping group as a group that critically reflects the educational values of Mandar culture.